The role of AMPK in cancer metabolism and its impact on the immunomodulation of the tumor microenvironment - Keerthana, Chenicheri Kizhakkeveettil; Rayginia, Tennyson Prakash; Shifana, Sadiq Chembothumparambil; Anto, Nikhil Ponnoor; Kalimuthu, Kalishwaralal; Isakov, Noah; Anto, Ruby John (Frontiers in Immunology, 2023)
Adenosine monophosphate-activated protein kinase (AMPK) is a key metabolic sensor that is pivotal for the maintenance of cellular energy homeostasis. AMPK contributes to diverse metabolic and physiological effects besides its fundamental role in glucose and lipid metabolism. Aberrancy in AMPK signaling is one of the determining factors which lead to the development of chronic diseases such as obesity, inflammation, diabetes, and cancer. The activation of AMPK and its downstream signaling cascades orchestrate dynamic changes in the tumor cellular bioenergetics. It is well documented that AMPK possesses a suppressor role in the context of tumor development and progression by modulating the inflammatory and metabolic pathways. In addition, AMPK plays a central role in potentiating the phenotypic and functional reprogramming of various classes of immune cells which reside in the tumor microenvironment (TME). Furthermore, AMPK-mediated inflammatory responses facilitate the recruitment of certain types of immune cells to the TME, which impedes the development, progression, and metastasis of cancer. Thus, AMPK appears to play an important role in the regulation of anti-tumor immune response by regulating the metabolic plasticity of various immune cells. AMPK effectuates the metabolic modulation of anti-tumor immunity via nutrient regulation in the TME and by virtue of its molecular crosstalk with major immune checkpoints. Several studies including that from our lab emphasize on the role of AMPK in regulating the anticancer effects of several phytochemicals, which are potential anticancer drug candidates. The scope of this review encompasses the significance of the AMPK signaling in cancer metabolism and its influence on the key drivers of immune responses within the TME, with a special emphasis on the potential use of phytochemicals to target AMPK and combat cancer by modulating the tumor metabolism.